Determinants of performance in a new test of planned agility for young elite basketball players - Delextrat, A.; Grosgeorge, B.; Bieuzen, F. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate the reliability and determinants of performance in a new test of planned agility in elite junior basketball players. Methods: Seventeen female (15.1 ± 0.4 y, 176.9 ± 11.2 cm, 65.7 ± 10.9 kg) and 42 male (14.9 ± 0.4 y, 193.7 ± 8.1 cm, 79.0 ± 12.0 kg) elite junior basketball players performed 5 fitness tests presented in a random order, including a 20-m sprint, a planned-agility test, a triple bilateral horizontal countermovement jump, and 2 triple unilateral horizontal countermovement jumps (with each leg separately). The novelty of the planned-agility test is that it included both offensive and defensive movements. The determinants of planned agility were assessed by a stepwise-regression analysis, and the reliability of the new test was evaluated by the intraclass correlation coefficient and the typical error of measurement. Results: The main results show good reliability of the new test of planned agility. In addition, the determinants of planned-agility performance were different between genders, with sprint performance explaining 74.8% of the variance for girls, while unilateral jump performance and body mass were the most important for boys, accounting for 24.0% and 8.9% of the variance, respectively, in planned agility. Conclusions: These results highlight a gender effect on the determinants of planned-agility performance in young elite basketball players and suggest that straight-line sprint and unilateral horizontal tests must be implemented to test elite junior players.